Exploring Alternative Disciplinary Measures To Manage Discipline In South African Primary Schools (Journal of Namibian Studies : History Politics Culture, 2025)
Primary schools in South Africa still struggle with discipline. Also, traditional discipline methods frequently fall short in addressing the underlying causes of ill-discipline and fail to provide a supportive learning environment. The study explores disciplinary measures currently used to manage ill-discipline in South African primary schools while fostering learners' academic performance, emotional growth, and general well-being. Since corporal punishment was abolished in South African schools, ill-discipline in schools has reached alarming heights despite guidelines for managing it. Many teachers still believe that corporal punishment is the only effective form of maintaining discipline in their classrooms. The question addressed is: “What disciplinary measures do schools apply to lessen ill- discipline?” A qualitative approach and a case study design were adopted for this study. Twelve participants were selected from 3 primary schools through a purposeful sampling approach. Data gathered through document review and interviews was analysed thematically. The study found that alternatives to corporal punishment were unproductive in managing ill-discipline and recommended schools to employ practical and feasible disciplinary measures. The findings offered teachers and policymakers practical suggestions to improve discipline measures and create a supportive learning environment.